Prospects And Challenges of Sharia Insurance (Takaful) for The Economy - Selvi Harvia Santri; Rosyidi Hamzah (Universitas Islam Sultan Agung, 2026)
This article examines the prospects and challenges of Islamic insurance for the Indonesian economy. The concept of Islamic insurance stems from differing views on conventional insurance, which lacks religious consultation. The growing demand for Islamic insurance (takaful) is supported by the majority of the Muslim population. However, Islamic insurance faces numerous challenges in its implementation. Islamic insurance is also believed to have excellent prospects for supporting the Indonesian economy. This paper aims to determine the prospects and challenges facing Islamic insurance in supporting the Indonesian economy. This research uses conceptual and legislative approaches. The paper concludes that the challenge facing Islamic insurance for the Indonesian economy is public non-compliance with Islamic insurance regulations and principles, which gives rise to legal issues within the community. The relatively new nature of Islamic insurance has led to a lack of reliable resources compared to conventional insurance institutions, which are far more experienced and possess reliable human resources. The potential of Islamic insurance for economic progress in Indonesia lies in its role as a non-financial institution for the community, functioning as a risk transfer agent. Most of the premium funds are invested through Sharia-compliant banks, which are useful in supporting the provision of capital for entrepreneurs, thereby helping people improve their standard of living and contributing to Indonesia's economic progress.